Enhancing the science process skills of the students in general college biology of the University of Eastern Philippines through DIAL (SPS) 2 - Abalon, Jenny B. (Animo Repository, 2002)
This study aims to find out whether the science process skills of the students in general college biology of the University of Eastern Philippines can be significantly enhanced by the method of directed inquiry known as Directed Inquiry Approach to Learning Science Process Skills and Scientific Problem Solving, [DIAL (SPS)2]. To attain this objective, an experimental group was compared with the control group that was exposed to the traditional teaching technique, the lecture-laboratory method. The experimental group was taught using DIAL (SPS)2 enriched with enhancement activities which involved science process skills on selected topics in general college biology course.A 40-item general college biology science process skills test constructed by the researcher served as both the pretest and the posttest. The data collected were then subjected to an analysis of covariance with the pretest as the covariate and the posttest as the dependent variable at the .05 level of significance. The result of the F-test at the .05 level of significance revealed that the experimental group performed significantly better than the control group on science process skills test. The above average students in verbal aptitude in both experimental and control groups performed significantly better than those who were below average in verbal aptitude.